2014
DOI: 10.1038/jid.2013.471
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin Sensitizes TRAIL-Resistant Melanoma Cells to TRAIL-Induced Apoptosis through ROS-Mediated Upregulation of Death Receptor 5 and Downregulation of Survivin

Abstract: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) has attracted considerable attention owing to its selective killing of tumor cells but not normal cells. Melanoma shows weak response to TRAIL because of its low level of TRAIL death receptors. Here, we investigated whether indomethacin, a nonsteroidal anti-inflammatory drug, can potentiate TRAIL-induced apoptosis in melanoma cells. We showed that indomethacin was capable of promoting TRAIL-induced cell death and apoptosis in A375 melanoma cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 53 publications
5
28
0
Order By: Relevance
“…Finally, caspase-3 protein expression and apoptosis induced by shikonin plus TRAIL were significantly attenuated after cells transfected with Si-DR5, and cell viability in same treatment could significantly promote compared with control. Previous study demonstrated that DR5 could induce JNK activation in colon cells [45], whereas most of other studies showed that ROS/JNK signalling mediated DR5 in various cell lines [46, 47], which were consistent with our results. In addition, we also found that Si-DR5 transfection has no effect on shikonin induced cell death.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Finally, caspase-3 protein expression and apoptosis induced by shikonin plus TRAIL were significantly attenuated after cells transfected with Si-DR5, and cell viability in same treatment could significantly promote compared with control. Previous study demonstrated that DR5 could induce JNK activation in colon cells [45], whereas most of other studies showed that ROS/JNK signalling mediated DR5 in various cell lines [46, 47], which were consistent with our results. In addition, we also found that Si-DR5 transfection has no effect on shikonin induced cell death.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, we also found that Si-DR5 transfection has no effect on shikonin induced cell death. This findings were similar to previous study [47]. These results suggested that shikonin-induced DR5 up-regulation was essential for TRAIL-enhanced effects of shikonin in RBE cells.…”
Section: Discussionsupporting
confidence: 83%
“…ROS participates in many intracellular pathological changes 6, 7. In accord with our and other previous studies, ROS triggers programmed cell death through the mitochondrial pathway, death receptor pathway, and endoplasmic reticulum stress‐mediated pathway 8, 9, 10. Previous studies indicated that AGEs induced endothelial cell apoptosis by exacerbating ROS‐mediated apoptosis 11…”
Section: Introductionsupporting
confidence: 91%
“…Natural compounds such as kurarinone (20), icaritin (21), withanolide E (22) were reported to downregulate cFLIP expression and subsequent sensitization of TRAIL-resistant cancer cells to TRAIL-induced apoptosis. Natural compounds, such as silibinin (23), gingerol (24) and indomethacin (25) were reported to possess both mechanisms of sensitizing TRAIL-resistant cancer cells.…”
Section: Introductionmentioning
confidence: 99%